What drives Africa`s export diversification? - Dick N. Kamuganga (Graduate Institute of International and Development Studies, 2012)
The primary purpose of this paper is to seek empirical answers to the above question. Using a highly disaggregated bilateral trade flows at HS 6 digit level for African countries for a period 1995-2009 and a conditional logit technique, I find 3 main empirical results. First, intra-Africa regional trade cooperation enhances the likelihood of an African nation exporting across the new-product, new-market margin. Second, I also find evidence that both product and market experience help to increase the chances of African exporters exporting on new-product and new market margins thus providing support for the learning effects hypothesis. The third result shows that infrastructure related trade frictions such as export costs; time to export; procedures to export as well as weak export supporting institutions have a negative effect on African export diversification. Similarly macroeconomic developments particularly exchange rate volatility, financial underdevelopments and inappropriate foreign direct investments hurt African nation's chances to diversify its exports. In policy terms this study suggests that for African exporters learning to export from regional markets before exploring major distant markets, a reduction in intra-African trade barriers, deepening and strengthening regional trade cooperation could be a significant channel for encouraging export diversification in Africa.
Keywords: F1; F13; F14; F15; 330; extensive margin of trade; firm heterogeneity; unilateral trade preferences & regional trade agreements; Handelspräferenzen; Handelsabkommen; Handelseffekt; Außenhandelsstruktur; Afrika